Challenges in managing multidrug-resistant infections among refugees: clinical experience during the Ukrainian war - Josu Urbieta-Mancisidor; Jesús-Martín Treviño-Theriot (European Journal of Case Reports in Internal Medicine)
The war in Ukraine, initiated in 2022, triggered a massive humanitarian crisis with millions displaced. This population exodus posed significant healthcare challenges, including the spread of infections caused by multidrug-resistant (MDR) bacteria. Factors such as disrupted healthcare services, inappropriate antimicrobial use and environmental contamination contributed to increased bacterial resistance. In this context, in 2023 an 86-year-old Ukrainian migrant was treated in a Spanish hospital for severe infections complicated by MDR bacteria. During hospitalisation, complex resistant strains of Pseudomonas aeruginosa and Klebsiella pneumoniae were identified. Treatment was guided by culture results, though infections recurred multiple times. A literature review indicated that infections among displaced Ukrainians commonly involve Gram-negative bacteria such as P. aeruginosa and K. pneumoniae, often exhibiting high resistance levels. This underscores the urgent need for infection control strategies, improved antibiotic stewardship and enhanced epidemiological surveillance. Additionally, it highlights the importance of international cooperation and networked efforts in managing antimicrobial resistance during conflicts and mass displacement.